Aspects of the rhizospheric microbiota and their interactions with the soil ecosystem - El Amrani Belkacem (Вавиловский журнал генетики и селекции, 2022)
Soil microbial communities play a key role in the evolution of the rhizosphere. In addition, proper exploration of these microbial resources represents a promising strategy that guarantees the health and sustainability of all ecosystems connected to the ground. Under the influence of environmental conditions, microbial communities can change compositions in terms of abundance and diversity. Beyond the descriptive level, the current orientation of microbial ecology is to link these structures to the functioning of ecosystems; specifically, to understand the effect of environmental factors on the functional structure of microbial communities in ecosystems. This review focuses on the main interactions between the indigenous soil microflora and the major constituents of the rhizosphere to understand, on the one hand, how microbial biodiversity can improve plant growth and maintain homeostasis of the rhizospheric ecosystem, on the other hand, how the maintenance and enrichment of plant biodiversity can contribute to the conservation of soil microbial diversity; knowing that these microorganisms are also controlled by the abiotic properties of the soil. Overall, understanding the dynamics of the rhizosphere microbiome is essential for developing innovative strategies in the field of protecting and maintaining the proper functioning of the soil ecosystem.